ESTABLECIMIENTO DEL Lolium multiflorum CON CINCO DENSIDADES SOBRE PASTURAS DEGRADADAS COMO UNA ALTERNATIVA A LA SIEMBRA DE CULTIVOS AGRÍCOLAS - Ordóñez F., José (2004)
The present study had the objective to evaluate the establishment of Italian Rye grass (Lolium multiflorum) under five densities of seeding (15, 30, 45, 60 and 75 kg of seed/ha) into degraded pastures invaded by kikuyu (Pennisetum clandestinum), as an alternative to rotations with agricultural cultivations. Each density was mixed with 3.0 kg/ ha of Lucerne seed (Ranger variety). The study was carried out at the “El Mantaro- IVITA” Research Station from March till July 2002. A land with degraded pasture that was grazed for seven years was mechanically prepared and the Italian Rye grass seed was vollied by hand. The fertilization was carried out with 60-20-0 of N-P2O5-K2O kg/ha thirty days after seedding. The statistical analysis was done using the randomized complete block design with three repetitions. The botanical composition before the first grazing (120 days after seeding) showed a significant increase (p<0.05) of the Italian Rye grass proportion (21.3 to 82.9% with the seeding density of 15 and 75 kg, respectively). The biomass production of Italian Rye grass significantly increased (p<0.05) with the increase of seeding density. It was concluded that the Italian Rye grass is better established into degraded areas invaded by kikuyu, when the seeding density was >30kg/ha.